THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, AND CORPORATE VALUE ON STOCK RETURN (PHARMACEUTICAL SUB SECTOR IN INDONESIA STOCK EXCHANGE 2015-2017) - Rinaldi Dwinanto Kosta Dinova; Aty Herawati (Dinasti International Journal of Education Management And Social Science, 2019)
This study aims to examine and analyze the influence of ROA, DER, PBV to return stock in a pharmaceutical company. Phenomena research on sub pharmaceutical sector because in recent years, especially in 2015-2017, pharmaceutical company stock returns decrease compared to other subsectors.The importance of this research was conducted to test and analyze the influence of ROA, DER, and PBV to return stock in companies in the Pharmaceutical Sector Sub listed in the Indonesia Stock Exchange. The study uses annual data for the observation period from 2015 up to 2017. The study was descriptive causality. The data used is the data panel that is a combination of annual time serial data and cross section which is processed using panel data regression analysis. The population is all Pharmaceutical Company listed on the Indonesia Stock Exchange in 2015 until 2017 with a sample of eight companies. The results of this study indicate that Return On Asset (ROA) has no effect and significant on stock returns, Debt to Equity Ratio (DER) has no significant negative effect on stock returns, Price to Book Value (PBV) significant negative effect on stock returns